Khanyayo village and Mkhambathi Nature Reserve, South Africa: a pragmatic qualitative investigation into attitudes towards a protected area. Issue 6 (3rd June 2019) - Queiros, Dorothy; Mearns, Kevin
ABSTRACT: Protected areas are often surrounded by impoverished communities. Biodiversity must be conserved while enabling community members' livelihoods. Benefit-sharing has been promoted as a means of fostering positive relationships between protected areas and local people, but views differ regarding which benefits have positive results; and which are most valued by communities themselves. This research investigates the attitudes of Khanyayo village towards Mkhambathi Nature Reserve on the Wild Coast of South Africa. A pragmatic, multi-method comparative qualitative approach was followed. Participants were local community members and key staff at Mkhambathi, who work with the community. Individual interviews, focus group interviews and an adapted nominal grouping technique were used, which aided triangulation. Results indicated a range of significant benefits and losses. Tangibles included access to natural resources, employment, infrastructure and training. More intangibles emerged though, such as enjoyment of reserve, involvement in the reserve, communication and environmental education. Losses predominantly related to prohibited or restricted access to natural resources. The comparison between the two participant groups yielded interesting insights. Knowing which benefits are most important to the community and aligning the perceptions of the people and the park staff could improve the relationship as well as enhance successful benefit-sharing.